Introduction: Content, Design and Structure of Major Databases with Historical Longitudinal Population Data - George Alter; Kees Mandemakers; Hélène Vézina (Historical Life Course Studies)
In recent years the development of historical databases reconstructing the lives of large populations accelerated. These considerable investments of time and money have greatly expanded possibilities for new research in history, demography, sociology, economics, and other disciplines. This special issue describes the content and design of 23 important historical databases. Authors were given the freedom to discuss a range of practical and technical decisions from evaluating archival sources to crowdsourcing data entry. The most common issue is nominative record linkage, but we find different choices between semi-automatic and fully automatic linkage techniques and various approaches for connecting diverse sources. Some databases describe special problems, like linking Chinese names, handwritten text recognition or the construction of a release in IDS-format. Other databases offer detailed descriptions of sources or discuss prospects for including new datasets.